3D Models of the NCI60 Cell Lines for Screening Oncology Compounds. (June 2017) - Selby, Mike; Delosh, Rene; Laudeman, Julie; Ogle, Chad; Reinhart, Russell; Silvers, Thomas; Lawrence, Scott; Kinders, Robert; Parchment, Ralph; Teicher, Beverly A.; Evans, David M.
The NCI60 cell line panel screen includes 60 human tumor cell lines derived from nine tumor types that has been used over the past 20+ years to screen small molecules, biologics, and natural products for activity. Cells in monolayer culture in 96-well plates are exposed to compounds for 48 h, and Sulforhodamine B is used to determine cell viability. Data analysis tools such as COMPARE allow classification of compounds based on the pattern of cell line response. However, many compounds highly active in monolayer cell culture fail to show efficacy in vivo. Therefore, we explored 3D culture of the NCI60 panel as a strategy to improve the predictive accuracy of the screen. 3D cultures more closely resemble tumors than monolayer cultures with tighter cell-cell contact and nutrient and oxygen gradients between the periphery and the center. We optimized the NCI60 cell line panel for generating 3D spheroids of a prespecified diameter (300–500 µm) in ultra-low attachment (ULA) plates. Spheroids were classified into four categories based on imaging, and concentration response of select agents in 2D and 3D models is presented.